Intracellular distribution and transcriptional regulation of Atlantic salmon (Salmo salar) Rab5c, 7a and 27a homologs by immune stimuli - Nepal, Arpita; Wolfson, Deanna; Ahluwalia, Balpreet Singh; Jensen, Ingvill; Jørgensen, Jorunn B; Iliev, Dimitar Borisov (Fish & Shellfish Immunology, 2020)
Rab GTPases control trafficking of intracellular vesicles and are key regulators of endocytic and secretory pathways. Due to their specific distribution, they may serve as markers for different endolysosomal compartments. Since Rab GTPases are involved in uptake and trafficking of endocytosed ligands and cell receptors, as well as secretion of immune mediators, they have been implicated in diverse immunological processes and their functions are often exploited by intracellular pathogens such as viruses. While Rab proteins have been studied extensively in mammals, their functions in vesicle trafficking in teleosts are not well known. In the present work, Atlantic salmon Rab5c, Rab7a and Rab27a homologs were studied in terms of intracellular distribution and gene expression. Structured illumination microscopy demonstrated that transgenic, GFP-tagged salmon Rab5c and Rab7a are, predominantly, located within early endosomes and late endosomes/lysosomes, respectively. In contrast, Rab27a showed a broader distribution, which indicates that it associates with diverse intracellular vesicles and organelles. Infection of salmon with Salmonid alphavirus subtype 3 (SAV3) enhanced the mRNA levels of all of the studied Rab isoforms in heart and head kidney and most of them were upregulated in spleen. This may reflect the capacity of the virus to exploit the functions of these rab proteins. It is also possible that the transcriptional regulation of Rab proteins in SAV3-infected organs may play a role in the antiviral immune response. The latter was further supported by in vitro experiments with adherent head kidney leukocytes. The expression of Rab5c and Rab27a was upregulated in these cells following stimulation with TLR ligands including CpG oligonucleotides and polyI:C. The expression of most of the analyzed Rab isoforms in the primary leukocytes was also enhanced by stimulation with type I IFN. Interestingly, IFN-gamma had a negative effect on Rab7a expression which may be linked to the priming activity of this cytokine on ...